Sewing machine magic : make the most of your machine : demystify presser feet and other accessories, tips and tricks for smooth sewing, 10 easy, creative projects /: make the most of your machine : demystify presser feet and other accessories, tips and tricks for smooth sewing, 10 easy, creative projects. (2017) - Lincecum, Steffani
No abstract available